PENILAIAN TINGKAT KINERJA KEUANGAN DENGAN MENGGUNAKAN ANALISIS RASIO KEUANGAN PADA PERUSAHAAN PT. ADARO ENERGY, TBK. PERIODE 2016-2018 - Helma Rizqikah Amir; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to study how to manage a company's finances. The purpose of this study is to analyze the company's financial performance at PT. Adaro Energy, Tbk. period 2016 to 2018 based on liquidity ratios, solvability, activity and profitability. The type of research used in this study is descriptive quantitative and the technique used is documentation techniques. The research data is obtained from the company's financial statements obtained through the company's official website. The results of this study indicate the results of the financial performance of PT. Adaro Energy, Tk for the 2016-2018 period based on profitability ratios can be said to be fulfilled because it is able to fulfill its short-term obligations. But solvency ratios can only be fulfilled with assets owned because capital is covered by debt. While the activity and profitability ratios are at a lower level, this is because the use of funds financed by debt is not used effectively, and te ability of capital invested in the form of funds to generate profits is relatively low.Keywords: Financial Performance; Liquidity; Solvency; Activity; Profitability